DIFFERENCE OF PATIENT SATISFACTION LEVELS TOO RIGHT BASED ON NUTRITION EXPERTISE PERFORMANCE IN BRSUD TABANAN AND WISMA PRASHANTI TABANAN HOSPITAL - Putu Nita Cintya Dewi; Ida Ayu Eka Padmiari; Ni Made Yuni Gumala (Jurnal Ilmu Gizi : Journal of Nutrition Science, 2021)
Satisfaction is one aspect of the assessment of the quality of hospital health services that has significance for patients in determining the next health behavior. Although this assessment has not been able to fully describe the quality or failure of services in the health sector, it is able to show the community's need for health services. The general objective of this study was to determine the differences in the level of satisfaction of inpatients with Performnce Nutritionists in the Tabanan BRSUD and Wisma Prashanti Tabanan Hospital. This type of research used is a type of descriptive study with cross sectional. The study population was all inpatients who received nutritional services from the Tabanan Regional General Hospital and Wisma Prashanti Hospital, while the samples were part of the population with criteria, new patients who were hospitalized and would get nutritional services with ordinary food for men and women who aged 18-55 years and able to be invited to communicate. Patients are in a conscious state, Willing to participate to be the subject of research in research, and based on the calculation of the sample number formula and this study as many as 94 people. The level of satisfaction of inpatient satisfaction with the performance of nutritionists at Tabanan BRSUD was 101.7% while the level of satisfaction of inpatients towards room nutritionist performance at Wisma Prashanti Tabanann Hospital was 102.3%. Keyword : Performance, Patient Satisfaction, Nutritionist